Keikutsertaan Dana Zakat dalam Pengentasan Kemiskinan di Indonesia - Ali Hardana (Bukhori: Kajian Ekonomi dan Keuangan Islam, 2022)
The Indonesian government through the National Zakat Agency (BAZNAS) has issued various programs in an effort to alleviate poverty in Indonesia.  Puprose: The Indonesian government through the National Zakat Agency (BAZNAS) has issued various programs in an effort to alleviate poverty in Indonesia. Methodology: This study aims to test the effectiveness of the zakat fund distribution programs by BAZNAS on poverty levels in Indonesia. In this study, the approach taken was a quantitative descriptive method using the EViews (Econometrics Views) analysis tool 10. This research uses OLS (Ordinary Least Square) method. Research using Secondary Data in the form of Monthly data for the period 2011-2019. Results: This study found that zakat distribution programs in the social and educational sectors have a significant negative effect on poverty levels in Indonesia.